Nation and nationalism in the West – The case of Germany - Bodrožić, Đuro (Sociološki pregled, 2024)
German national consciousness, when compared to other nations, was formed later, but it took less time to mature and appear in the fullness of its requests. While the process of national maturation and promotion/elevation of the national idea among other nations lasted one whole century or even longer, among Germans it occurred in a substantially shorter period. For that to happen, there had to be assumptions created through a longer period of time. Here we point to the factors, political and cultural, as integral part of the historical process in the formation of German nation, which finally determined its nature and the character of German nationalism.
Keywords: Germany; Germans; romanticism; reformation; Martin Luther; French Revolution; Prussia; Austria